2017
DOI: 10.1111/maps.12931
|View full text |Cite
|
Sign up to set email alerts
|

Petrogenesis and shock metamorphism of the enriched lherzolitic shergottite Northwest Africa 7755

Abstract: Northwest Africa (NWA) 7755 is a newly found enriched lherzolitic shergottite. Here, we report its detailed petrography and mineralogy. NWA 7755 contains both poikilitic and non-poikilitic lithologies. Olivine has different compositional ranges in the poikilitic and non-poikilitic lithologies, Fa 30-39 and Fa 37-40 , respectively. Pyroxene in the non-poikilitic lithology is systematically Fe-richer than that in the poikilitic lithology. The chromite grains in non-poikilitic lithology are highly Ti-richer than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 76 publications
2
18
0
Order By: Relevance
“…Tuite was proposed to form from decomposition of apatite or solid-state phase transformation of merrillite (Murayama et al, 1986;Xie et al, 2016;Xie et al, 2002;Xie et al, 2013). Some tuite grains in Suizhou (Xie et al, 2016) and NWA 7755 (Wang et al, 2017) were found coexisting with Cl-rich apatite, with a Cl content of up to ~ 3.9 wt%, consistent with possibility that they formed through decomposition of adjacent chlorapatite. However, the ideal formula of tuite, Ca3(PO4)2, similar to extraterrestrial merrillite, does not contain Cl or other halogens (Jolliff et al, 2006;McCubbin et al, 2014).…”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…Tuite was proposed to form from decomposition of apatite or solid-state phase transformation of merrillite (Murayama et al, 1986;Xie et al, 2016;Xie et al, 2002;Xie et al, 2013). Some tuite grains in Suizhou (Xie et al, 2016) and NWA 7755 (Wang et al, 2017) were found coexisting with Cl-rich apatite, with a Cl content of up to ~ 3.9 wt%, consistent with possibility that they formed through decomposition of adjacent chlorapatite. However, the ideal formula of tuite, Ca3(PO4)2, similar to extraterrestrial merrillite, does not contain Cl or other halogens (Jolliff et al, 2006;McCubbin et al, 2014).…”
Section: Introductionmentioning
confidence: 57%
“…The high-pressure minerals discovered in these extraterrestrial natural samples could reveal the impact history on their parent bodies and provide insights into the phase transformation mechanisms in the interior of Earth (Petrova and Grokhovsky, 2019). To date, high-pressure polymorphs of olivine (Binns et al, 1969;Chen et al, 2004;Ma et al, 2016;Miyahara et al, 2008;Putnis and Price, 1979), pyroxene (Chen et al, 1996;Sharp et al, 1997;Tomioka and Fujino, 1999;Tschauner et al, 2014), feldspar (Fritz et al, 2020;Gillet et al, 2000;Liu, 1978;Ma et al, 2018;Tschauner et al, 2021), zircon (Glass et al, 2002;Xing et al, 2020), silica (El Goresy et al, 2004;El Goresy et al, 2000b;Hu et al, 2020;Miyahara et al, 2014;Ohtani et al, 2011;Sharp et al, 1999), chromite (Chen et al, 2003;Ma et al, 2019), and Ca phosphate (Wang et al, 2017;Xie et al, 2002;Xie et al, 2013) have been reported from various meteorites displaying shock effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basaltic and olivine‐phyric shergottites include many kinds of high‐pressure minerals (e.g., Beck et al., 2004; Sharp et al., 2019). In contrast, only a few lherzolitic shergottites contain high‐pressure minerals, although shock‐induced melting textures and maskelynite are pervasively found in them (Imae & Ikeda, 2010; Mikouchi, 2005; Ozawa et al., 2011; Wang et al., 2017). Regions of apatite (or merrillite) grains were transformed into the high‐pressure polymorph tuite (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NWA 11004 contains 3‐ to 5‐mm‐sized poikilitic pyroxene oikocrysts enclosing 40‐ to 400‐μm‐sized olivine chadacrysts. The poikilitic texture occurs in shergottites (e.g., Wang et al, 2017), pyroxene phenocrysts in chondrules (e.g., Scott & Taylor, 1983), and some OC impact melt rocks (e.g., Mittlefehldt & Lindstrom, 2001; Wu & Hsu, 2019), all of which crystallized from melts. Pyroxene and associated olivine grains crystallized from OC impact melt rocks usually show (1) a pronounced positive linear trend between TiO 2 and Al 2 O 3 in pyroxene (e.g., L‐impact melt rock PAT 91501, Mittlefehldt & Lindstrom, 2001; L‐melt rock NWA 11042, Wu & Hsu, 2019) and (2) relatively ferroan‐rich silicates at the upper end of the corresponding chondritic compositional range (e.g., olivine Fa 25.2–26.8 for L‐impact melt rock PAT 91501 vs. olivine Fa 22–26 for typical L chondrites; Brearley & Jones, 1998, Mittlefehldt & Lindstrom, 2001).…”
Section: Discussionmentioning
confidence: 99%